Pengembangan Buku Ajar Statistik Menggunakan Aplikasi SPSS sebagai Self-¬Education Mahasiswa - Sufri Sufri; Feri Tiona Pasaribu (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The purpose of this research is to produce statistical textbooks using the SPSS (Statistical Product and Service Solution) application as self-education for students who meet the criteria of validity, practicality and effectiveness. This research is a development research that uses the ADDIE development model which implements an Analyze, Design, Develop, Implement, and Evaluate stage. The results obtained in this study are the quality of textbook development results from the results of material validation analysis with a percentage of 90%, design validation analysis with a percentage of 88.9% fulfilling very valid criteria. The results of the questionnaire analysis show that the textbook meets the very practical criteria. Based on the results of the analysis of the lecturer assessment questionnaire with a percentage of 90%, the results of the small group trial questionnaire analysis with a percentage of 79.50%. Thus, statistical textbooks using the SPSS (Statistical Product and Service Solution) application meet the valid and practical criteria.